Seeing Through Fishers' Lenses: Exploring Marine Ecological Changes Within Mafia Island Marine Park, Tanzania. (3rd May 2016) - Moshy, Victoria H.; Bryceson, Ian
Insights from traditional ecological knowledge (TEK) of the marine environment are difficult to integrate into conventional science knowledge (CSK) initiatives. Where TEK is integrated into CSK at all, it is usually either marginalized or restricted to CSK modes of interpretation, hence limiting its potential contribution to the understanding of social-ecological systems. This study uses semi-directive interviews, direct observations, and structured open-ended questionnaires ( n = 103) to explore TEK of marine ecological changes occurring within the Mafia Island Marine Park, Tanzania, and factors contributing to these changes. It illuminates TEK insights that can be valuable in parallel with CSK to provide a more nuanced understanding of ecological changes. In some areas, fishers observed coral reef growth, increased fish abundance, and increased sea temperatures, whereas in others, they reported decreases in sea level, coral cover, fish abundance, catch composition, catch quantities, and fish size. They associated these changes with interrelated factors emanating from environmental processes, conservation outcomes, marketing constraints, population dynamics, and disappearance of cultural traditions. Utilizing TEK without restricting it to CSK modes of interpretation has the potential to improve CSK initiatives by promoting complementarity and mutual enrichment between the two kinds of knowledge, thereby contributing new insights that may enhance adaptive management and resilience in social-ecological systems.